2018
DOI: 10.1111/jan.13766
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of complications between peripheral arm ports and central chest ports: A meta‐analysis

Abstract: Arm ports are a safe option beside chest ports for adult patients with malignancy, especially in patients with head-neck cancer or breast cancer. Patients should be well informed of the advantages and disadvantages of different vascular access devices and provided a choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…The clinical nursing pathway had also achieved good results in the nursing of patients with intracerebral hemorrhage [ 24 ]. Evidence based nursing was based on science, aiming at the detailed problems found in the process of nursing practice, making nursing decisions, and guiding clinical nursing work by querying and collecting materials [ 25 ]. Using the concept of evidence-based medicine in nursing work could better expand the thinking of nurses so as to carry out nursing work more scientifically and reasonably.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical nursing pathway had also achieved good results in the nursing of patients with intracerebral hemorrhage [ 24 ]. Evidence based nursing was based on science, aiming at the detailed problems found in the process of nursing practice, making nursing decisions, and guiding clinical nursing work by querying and collecting materials [ 25 ]. Using the concept of evidence-based medicine in nursing work could better expand the thinking of nurses so as to carry out nursing work more scientifically and reasonably.…”
Section: Discussionmentioning
confidence: 99%
“…Although chest ports inserted via internal jugular vein or subclavian vein are considered optimal, other insertion sites such as upper arm to decrease catheter-related complications have also been explored [31,32]. Peripheral arm ports are comparable to the chest ports in arterial injury and have a prominent advantage of less pneumothorax [33]. Due to safety and cost-effectiveness related to bedside insertion, arm ports have been increasingly applied over recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Chest ports showed the most excellent results in terms of complication rates and catheter indwelling time. A previous study suggested that peripheral arm ports were comparable to chest ports in arterial injuries and had the prominent advantage of less pneumothorax [23]. Since we used ultrasound guidance in all cases, we did not encounter arterial injury or pneumothorax.…”
Section: Plos Onementioning
confidence: 93%